Integration of Tradition and Modernization of Education at the Riyadhul Jannah Islamic Boarding School, Subang - Gunawan, Peri; Mohammad Rusli Hamdani; Muhamad Yasir; Asep Komarudin; Andewi Suhartini (The Magister of Islamic Education IAIN Pontianak, 2026)
Islamic boarding schools (pesantren), as the oldest Islamic educational institutions in Indonesia, face major challenges in the era of globalization, which demands adaptation without the loss of identity. This study examines the process of pesantren modernization through a case study of the Riyadhul Jannah Islamic Education Foundation in Subang, which has undergone significant transformation since its establishment in 1996. Employing a descriptive qualitative approach through document and literature analysis, this research reveals how modern pesantren have successfully integrated traditional Islamic values with the demands of contemporary education. The findings indicate that Riyadhul Jannah has transformed from a single pesantren into a foundation overseeing 32 educational institutions, implementing an integrated pesantren–national curriculum model, developing students’ entrepreneurship, and applying professional, technology-based management. The vision, “Creating a Muttaqin Generation that is Intellectual, and Intellectuals who are Muttaqin,” reflects the success of balancing spiritual depth (faith and piety/IMTAQ) with academic excellence (science and technology/IPTEK). This study concludes that successful pesantren modernization is characterized by the ability to integrate the tradition of tafaqquh fiddin with modern educational innovation, institutional diversification, economic self-reliance, and a global orientation without sacrificing the core values of pesantren education